The effect of subarachnoid sodium nitroprusside on the prevention of vasospasm in subarachnoid haemorrhage - Pachl, J; Haninec, P; Tencer, T; Mizner, P; Houst'ava, L; Tomás, R; Waldauf, P (Acta neurochirurgica. Supplement, 2005)
OBJECTIVE: The aim of this study was to evaluate the effect of preventive and therapeutic use of subarachnoid sodium nitroprusside (SNP) administration in patients with non-traumatic subarachnoid haemorrhage (SAH). METHODS: All consecutive adult patients admitted in the period 2000-2003 with SAH, Hunt-Hess grade I-IV, indicated for neurosurgical intervention, were enrolled in the study. In the postoperative period they were treated with mechanical ventilation and triple H protocol with nimodipine. Subarachnoid preventive SNP was administred in initial dose of 1 mg by catheter inserted into basal cisterns during the neurosurgical procedure. The timing of following dosage was directed by the changes of respiratory parameters of brain tissue in the region of interest by multiparameter sensor (Codman Neurotrend) and findings of blood flow velocity on the level of circle of Willis were measured by transcranial doppler ultrasonography (TCD). RESULTS: 17 patients were enrolled to study. All patients survived. No brain infarction developed. The increase blood flow velocity was found in three patients. CONCLUSION: Preventive subarachnoid use of SNP in combination with multimodal monitoring might be a possible preventive strategy. Its efficacy has to be proved on a greater group of patients in the future. The therapeutical use of SNP requires an increase in application rate.
Keywords: senioři; subarachnoidální prostor; výsledek terapie; Vasospasm, Intracranial; Middle Aged; Injections, Intraventricular; mužské pohlaví; subarachnoidální krvácení; Adult; Subarachnoid Space; Catheterization; nitroprusid; intrakraniální vazospazmus; ženské pohlaví; Humans; injekce intraventrikulární; Nitroprusside; vazodilatancia; Vasodilator Agents; lidé středního věku; Subarachnoid Hemorrhage; dospělí; Female; Aged; katetrizace; Treatment Outcome; lidé; Male